Different predictive values of microvessel density for biochemical recurrence among different PCa populations: A systematic review and meta‐analysis - Jinjiang Jiang; Jinze Li; Xingyu Xiong; Shiyu Zhang; Daqing Tan; Lu Yang; Qiang Wei (Cancer Medicine)
Abstract Background Several studies have explored the relationship between intratumoral microvessel density (MVD) and the risk of postoperative biochemical recurrence (BCR) in prostate cancer (PCa), although the results are contradictory. Therefore, we conducted a meta‐analysis to investigate the effect of MVD on BCR in PCa. Method We searched PubMed, MEDLINE, Science Direct/Elsevier, the Cochrane Library, CNKI, and EMBase databases from inception through January 2022, with no year or language restrictions, and used NOS guidelines to evaluate the quality of the 19 eligible studies. The derived hazard ratio (HR) and 95% confidence interval (95%CI) were used to assess each endpoint. Data synthesis was performed with RevMan to assess the prognostic value of MVD in PCa and its heterogeneity, while the publication bias was examined using STATA 16.0. Results Our meta‐analysis included 19 articles (4 for T1‐2, 6 for T1‐3, and 9 for T1‐4) on postoperative biochemical recurrence of PCa, among which, 3933 patients were pooled. The predictive ability of intratumoral MVD for different stages of PCa on BCR was T1‐2 (HR, 2.46; 95% CI, 1.08–5.58; p = 0.03; I2 = 83%), T1‐3 (HR, 2.38, 95% CI, 1.41–4.01; p = 0.001; I2 = 82%), T1‐4 (HR, 1.61; 95% CI, 1.19–2.19; p = 0.002; I2 = 61%).The subgroup analyses based on European and immunohistochemical antibody none‐factor VII were consistent with primary one. Sensitivity analysis excluding those studies judged to be at high risk of bias in T1‐2 showed a HR of 2.99[1.70,5.27] (I2 = 38%, p = 0.0001), demonstrating the robustness of risk estimates of MVD for the assessment of biochemical recurrence. Conclusion Microvessel density is a predictor of BCR among patients with PCa, and earlier T stage PCa with a stronger MVD is associated with BCR. Further studies are needed to investigate neoangiogenesis in different T stages of PCa and whether MVD will be of benefit to the EAU‐recommended tool for biochemical recurrence risk assessment.